2004
DOI: 10.1063/1.1753572
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent self-diffusion of liquids in nanopores: A nuclear magnetic resonance study

Abstract: Nuclear magnetic resonance has been applied to study the details of molecular motion of low-molecular-weight polar and nonpolar organic liquids in nanoporous silicon crystals of straight cylindrical pore morphology at different pore loadings. Effective self-diffusion coefficients as obtained using the pulsed field gradient nuclear magnetic resonance method were found to pass through a maximum with increasing concentration for all liquids under study. Taking account of a concentration-dependent coexistence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 36 publications
(44 reference statements)
7
89
0
Order By: Relevance
“…Our findings compare well with experimental results on the dynamics of "conventional" liquid condensates [8,84,[98][99][100][101][102][103] confined in nanoporous media. In particular, the observation of distinct core and shell molecular mobilities is also in good agreement with experimental studies on pore-confined liquid crystalline systems presented in the past [7, 58-66, 69, 70], most prominently with the work by Aliev et al discussed in the introduction.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings compare well with experimental results on the dynamics of "conventional" liquid condensates [8,84,[98][99][100][101][102][103] confined in nanoporous media. In particular, the observation of distinct core and shell molecular mobilities is also in good agreement with experimental studies on pore-confined liquid crystalline systems presented in the past [7, 58-66, 69, 70], most prominently with the work by Aliev et al discussed in the introduction.…”
Section: Discussionsupporting
confidence: 79%
“…Being intrinsically related to the different density distributions at equal external conditions, this was expected to show up as well in the patterns of molecular propagation. Indeed, our first experiments with mesoporous silicon have shown that, in parallel to adsorption hysteresis, there is also the phenomenon of "diffusion hysteresis" (Naumov et al 2007;Valiullin et al 2004). The diffusivities measured on the adsorption and desorption branches as a function of the external gas pressure exhibit quite a complex behavior.…”
Section: Diffusivity As a Function Of The Pore Fillingmentioning
confidence: 97%
“…In Ref. 109, by relating p g to the pore filling θ , these dependencies are shown to be readily modeled on the basis of equation (24). It was thus demonstrated that, in line with beds of microporous host materials, 37 the dependency of the effective diffusivities on the degree of pore filling in mesoporous materials is as well determined by the particular shape of the sorption isotherms.…”
Section: Diffusion In Mesoporous Materialsmentioning
confidence: 93%